2021
DOI: 10.1186/s12935-021-02132-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of m6A methylation modification in esophageal squamous cell carcinoma

Abstract: In recent years, with the development of RNA sequencing technology and bioinformatics methods, the epigenetic modification of RNA based on N6-methyladenosine (m6A) has gradually become a research hotspot in the field of bioscience. m6A is the most abundant internal modification in eukaryotic messenger RNAs (mRNAs). m6A methylation modification can dynamically and reversibly regulate RNA transport, localization, translation and degradation through the interaction of methyltransferase, demethylase and reading pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Li J showed that in the pathophysiology of ESCC, ALKBH5 acts as a tumor suppressor ( Li et al, 2021 ). Due to advances in biological technologies such as high-throughput sequencing and the discovery of abnormal expression of METTL3, ALKBH5, and FTO, the role of m 6 A methylation in ESCC has gradually been revealed ( Zhang et al, 2021 ). The insidious onset of ESCC is primarily responsible for the patients’ poor prognosis, and by the time of diagnosis, the majority had advanced to the middle and late stages of lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Li J showed that in the pathophysiology of ESCC, ALKBH5 acts as a tumor suppressor ( Li et al, 2021 ). Due to advances in biological technologies such as high-throughput sequencing and the discovery of abnormal expression of METTL3, ALKBH5, and FTO, the role of m 6 A methylation in ESCC has gradually been revealed ( Zhang et al, 2021 ). The insidious onset of ESCC is primarily responsible for the patients’ poor prognosis, and by the time of diagnosis, the majority had advanced to the middle and late stages of lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) is the most common epigenetic RNA modification that plays an important role in the regulation of malignancies ( 2 ). Despite the potential of m6A for the diagnosis and treatment of ESCA ( 3 , 4 ), its potential targets and mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently identified m6A ‘readers’ include YTH domain family members (YTHDC1, YTHDC2, YTHDF1, YTHDF2 and YTHDF3), heterogeneous nuclear ribonucleoprotein (HNRNP) family members (HNRNPC and HNRNPA2B1), insulin-like growth factor 2 mRNA-binding proteins (IGF2BP1, IGF2BP2 and IGF2BP3), fragile X mental retardation 1 (FMR1) and leucine rich pentatricopeptide repeat containing (LRPPRC) [ 48 , 64 ]. These ‘readers’ possess the ability to recognize m6A modifications in RNAs and generate functional signals [ 65 ].…”
Section: Molecular Basis For M6a Modificationmentioning
confidence: 99%
“…Stable complexes are the main gateway to epigenetic methylation machinery. In addition to the KIAA1429/WTAP complex, one known complex of m6A methyltransferases consists of WTAP, METTL3 and METTL14 [ 53 , 64 ]. Although it forms a protein complex to coordinate with WTAP/METTL14 in m6A modification, METTL3 seems at be the core of this process in endometrioid EOC, stemming from the fact that knockdown of METTL3, but not WTAP/METTL14, decreased the m6A levels of associated targets (determined in vitro by RIP-qPCR) [ 76 ].…”
Section: Biological Functions Of M6a Related Regulators In Ovarian Cancermentioning
confidence: 99%